The Body of Evidence Corpses and Proofs in Early Modern European Medicine - Paolo de Ceglie, Francesco (Medieval and Early Modern Philosophy and Science, 2020)
In The Body of Evidence. Corpses and Proofs in Early Modern European Medicine Francesco Paolo de Ceglia offers an overview of the evolution of the science of the 'signs of the corpse', from necromancy to forensic medicine. Readership: The volume is aimed at scholars and specialized libraries in the historical field. Rich in original anecdotes, it can also be read easily by inquisitive people.